2014
DOI: 10.1016/j.ymgme.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Inborn errors of metabolism identified via newborn screening: Ten-year incidence data and costs of nutritional interventions for research agenda planning

Abstract: Inborn errors of metabolism (IEM) are genetic disorders in which specific enzyme defects interfere with the normal metabolism of exogenous (dietary) or endogenous protein, carbohydrate, or fat. In the U.S., many IEM are detected through state newborn screening (NBS) programs. To inform research on IEM and provide necessary resources for researchers, we are providing: tabulation of ten-year state NBS data for selected IEM detected through NBS; costs of medical foods used in the management of IEM; and an assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 22 publications
(24 reference statements)
1
79
0
1
Order By: Relevance
“…60,65 Taking all the reported cases detected by NBS in the USA from 2001 to 2010, the incidence of MCAD was 1 in 17,759. 66 In Massachusetts, approximately 1 out of 15,000 infants screened was diagnosed with MCAD, almost identical to the 1:14,000 frequency of phenylketonuria. 31 In Pennsylvania and Bavaria, the MCAD frequency from the introduction of NBS has been estimated to be even greater at 1:8,000 and 1:9,000, respectively.…”
Section: Molecular Aspectsmentioning
confidence: 99%
“…60,65 Taking all the reported cases detected by NBS in the USA from 2001 to 2010, the incidence of MCAD was 1 in 17,759. 66 In Massachusetts, approximately 1 out of 15,000 infants screened was diagnosed with MCAD, almost identical to the 1:14,000 frequency of phenylketonuria. 31 In Pennsylvania and Bavaria, the MCAD frequency from the introduction of NBS has been estimated to be even greater at 1:8,000 and 1:9,000, respectively.…”
Section: Molecular Aspectsmentioning
confidence: 99%
“…A recent study by Therrell et al [10] found that the frequency of primary carnitine deficiency among newborn screening programs in the USA is 1: 142,000. However, the frequency of mutations (nonsense, splicing and expressed missense only) in 60,000 normal individuals (carriers) in the exac browser (http://exac.broadinstitute.…”
Section: Shortcomings Of Newborn Screeningmentioning
confidence: 99%
“…The incidence of primary carnitine deficiency varies with a frequency of approximately 1: 40,000 newborns in Japan [8] , 1: 37,000-1: 100,000 newborns in Australia [9] and 1: 142,000 in the USA [10] . The highest incidence (1: 300) has been reported in the Faroe Islands, an archipelago that remained geographically isolated for centuries [11] .…”
Section: The Need To Screen For and Treat Primary Carnitine Deficiencymentioning
confidence: 99%
“…Primary carnitine deficiency has a frequency of 1:40,000 in Japan [12], 1:120,000 in Australia [13] and 1:140,000 in the USA [14]. The disease is very common in the Faroe Islands with a prevalence of 1:300 [15].…”
Section: Molecular Bases and Prevalence Of Primary Carnitine Deficiencymentioning
confidence: 99%